Risk Factors for Hypothalamic Obesity in Patients With Adult-Onset Craniopharyngioma: A Consecutive Series of 120 Cases - Wu, Wei; Sun, Quanya; Zhu, Xiaoming; Xiang, Boni; Zhang, Qiongyue; Miao, Qing; Wang, Yongfei; Li, Yiming; Ye, Hongying (Frontiers in Endocrinology, 2021)
Context: Hypothalamic obesity (HO) is a severe complication following craniopharyngioma, but studies regarding the sequelae in adult-onset patients with craniopharyngioma are sparse. Objective: The objective of the study was to describe weight changes after surgical treatment in adult-onset craniopharyngioma patients and to analyze risk factors for postoperative weight gain and HO. Subjects and method: A retrospective analysis was conducted of 120 adult-onset patients who underwent surgery for craniopharyngioma and follow-up at the authors’ institution between January 2018 and September 2020. Clinical characteristics, anthropometric data, image features, treatment modalities and endocrine indices were collected. Multivariable logistic regression analysis was used to identify independent risk factors for postoperative weight gain and HO. Results: 49 (40.8%) patients had clinically meaningful weight gain (≥5%) in a median follow-up time of 12.0 months (range 1.0-41.0 months) after surgery. The mean postoperative weight gain in this subgroup was 17.59±12.28 (%). Weight gain continues in the first year following surgery. Patients with lower preoperative BMI (OR 0.78, 95% CI [0.67-0.90], P=0.001) and the adamantinomatous subtype (OR 3.46, 95% CI [1.02-11.76], P=0.047) were more likely to experience postoperative weight gain ≥5%. The prevalence of HO was 19.2% preoperatively, and increased to 29.2% at last follow-up postoperatively. Only preoperative BMI (OR 2.51, 95% CI [1.64-3.85], P<0.001) was identified as an independent risk factor for postoperative HO. Conclusions: HO is a common complication in patients with adult-onset craniopharyngioma. Patients with higher preoperative BMI had a greater risk for developing HO postoperatively.